A knowledge-based view of process improvement: a mixed methods study into the role of social networks and knowledge acquisition - Marzec, Peter Edward (2013)
The goal of this dissertation is to motivate a Knowledge-Based View of Process Improvement. In doing so, it advocates that acquiring and exploiting knowledge is the key to achieving and sustaining competitive advantage. The heightened competitive landscape firms now operate in, is not only driving the need for process improvement in order for firms to stay competitive, but also the need to acquire knowledge from external sources as firms may no longer have the luxury of developing solely from internally generated ideas. With the understanding that knowledge resides in and is created by individuals, and in line with broader trends towards more micro-views of the firm, the research looks at process improvement and knowledge acquisition at the individual level.